2019
DOI: 10.1039/c8np00054a
|View full text |Cite
|
Sign up to set email alerts
|

Native roles of Baeyer–Villiger monooxygenases in the microbial metabolism of natural compounds

Abstract: Covering: up to end of June 2018Baeyer-Villiger monooxygenases (BVMOs) are flavin-dependent enzymes that catalyse the oxidation of ketones and cyclic ketones to esters and lactones, respectively, by using molecular oxygen and NAD(P)H. BVMOs also catalyse sulfoxidations and N-oxidations. BVMOs are widely studied as attractive biocatalysts, but also catalyse key reactions in metabolic pathways of the organisms from which they are sourced. BVMOs are involved in the primary metabolism of atypical carbon sources, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 178 publications
0
45
0
1
Order By: Relevance
“…BVMOs have received a high level of attention due to being attractive candidates for "green synthesis" on account of their relatively relaxed substrate profile, high chemoselectivity and preference for mild catalytic conditions. These characteristics facilitate sustainable synthesis platforms, and as a result, there has been an increasing number of reports regarding the engineering of BVMOs [46,47].…”
Section: Baeyer-villiger Monooxygenasesmentioning
confidence: 99%
“…BVMOs have received a high level of attention due to being attractive candidates for "green synthesis" on account of their relatively relaxed substrate profile, high chemoselectivity and preference for mild catalytic conditions. These characteristics facilitate sustainable synthesis platforms, and as a result, there has been an increasing number of reports regarding the engineering of BVMOs [46,47].…”
Section: Baeyer-villiger Monooxygenasesmentioning
confidence: 99%
“…The ClusterFinder algorithm also employs a more global view to detecting NP pathways and is concerned with identifying genomic regions that are enriched in Pfam domains that occur frequently in known NP BGCs, rather than signature biosynthetic genes 216 . Cryptic clusters can be identified in this way because biosynthetic pathways that produce entirely different products employ members of many of the same enzyme superfamilies 115,116,146,[217][218][219][220] . This approach was successfully applied in a systematic effort to identify and characterize BGCs encoded across 1,154 diverse bacterial genomes and led to the identification of a previously unrecognized family of arylpolyene-encoding BGCs that are distributed across a wide range of bacterial phyla 216 .…”
Section: Decrypting Biosynthetic 'Dark Matter'mentioning
confidence: 99%
“…Besides, BhmJ or BhmK are functional in heterologous hosts, suggesting their great potential as useful catalysts for industrial or pharmaceutical applications. [53][54][55][56][57] In conclusion, our study revealed the coordinated action of BhmJ/BhmK/BhmG for BHMs production in CB02009-R-5 assisted by a rapid ribosome engineering approach. We also revealed distinct biosynthetic mechanisms for two unusual methyl groups in BHMs, including (1) BhmG-catalyzed C-methylation and (2) incorporation of a non-proteinogenic amino acid (2S,5S)-5-methylproline.…”
mentioning
confidence: 61%